2016
DOI: 10.4103/0972-5229.175931
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinical pharmacist in an Indian Intensive Care Unit

Abstract: Background and Objectives:A critically ill patient is treated and reviewed by physicians from different specialties; hence, polypharmacy is a very common. This study was conducted to assess the impact and effectiveness of having a clinical pharmacist in an Indian Intensive Care Unit (ICU). It also evaluates the clinical pharmacist interventions with a focus on optimizing the quality of pharmacotherapy and patient safety.Materials and Methods:The prospective, observational study was carried out in medical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
11
1
4
Order By: Relevance
“…Drug dosing adjustment done by the clinical pharmacist included 140 (11.9%) renal dose, 62 (5.2%) hepatic dose, 17 (1.4%) pediatric dose, and 104 (8.8%) insulin dosing modi ications. Clinical pharmacist as a part of multidisciplinary team in our study was associated with a substantially lower rate of adverse drug event caused by medication errors, drug interactions, and drug incompatibilities" [13]. Luisetto M et al, write that (2017) "We think that the clinical ph.…”
Section: Methodsmentioning
confidence: 73%
See 1 more Smart Citation
“…Drug dosing adjustment done by the clinical pharmacist included 140 (11.9%) renal dose, 62 (5.2%) hepatic dose, 17 (1.4%) pediatric dose, and 104 (8.8%) insulin dosing modi ications. Clinical pharmacist as a part of multidisciplinary team in our study was associated with a substantially lower rate of adverse drug event caused by medication errors, drug interactions, and drug incompatibilities" [13]. Luisetto M et al, write that (2017) "We think that the clinical ph.…”
Section: Methodsmentioning
confidence: 73%
“…team and remained in the ICU for consultation in the morning, and was available on call throughout the day. The rate of preventable ordering ADEs decreased by 66% from 10.4 per 1000 patient-days (95% con idence interval [CI], [7][8][9][10][11][12][13][14] before the intervention to 3.5 (95% CI, 1-5; P<0.001) after the intervention. In the control unit, the rate was essentially unchanged during the same time periods: 10.9 (95% CI, 6-16) and 12.4 (95% CI, [8][9][10][11][12][13][14][15][16][17] per 1000 patient-days.…”
Section: Methodsmentioning
confidence: 99%
“…13 Não foram realizadas intervenções no referido estudo, pois de acordo com autores, algumas interações medicamentosas podem não ser clinicamente relevantes para todos os pacientes. 14 No presente estudo, foi observado que 2,26% das prescrições apresentavam incompatibilidades, além disso, realizou-se intervenção de reconciliação medicamentosa em 4,52% das prescrições, números estes mais expressivos do que no estudo realizado no Hospital Israelita Albert Einstein, que das 3.542 prescrições analisadas, foram realizadas 1.238 intervenções de natureza diversa, sendo que 4% eram referentes a incompatibilidades e 0,16% foram de reconciliação e inferior a dados de incompatibilidade observados por outros autores, onde revelou 13,7% de incompatibilidades.…”
Section: Resultsunclassified
“…14 No presente estudo, foi observado que 2,26% das prescrições apresentavam incompatibilidades, além disso, realizou-se intervenção de reconciliação medicamentosa em 4,52% das prescrições, números estes mais expressivos do que no estudo realizado no Hospital Israelita Albert Einstein, que das 3.542 prescrições analisadas, foram realizadas 1.238 intervenções de natureza diversa, sendo que 4% eram referentes a incompatibilidades e 0,16% foram de reconciliação e inferior a dados de incompatibilidade observados por outros autores, onde revelou 13,7% de incompatibilidades. 13,15 Outro autor descreveu que 41,3% dos pacientes avaliados relataram fazer uso de medicamentos em casa, e nestes foi realizado reconciliação medicamentosa. 8 Um estudo de coorte, prospectivo e transversal, realizado na República Checa, com 82 pacientes, verificou que 6,82% dos medicamentos prescritos foram considerados incompatíveis.…”
Section: Resultsunclassified
“…Several studies demonstrated a significant role of a clinical pharmacist (CP) as a full member of a multidisciplinary team in the intensive care unit (ICU) [1][2][3][4][5]. Full membership of a CP in the ICU team includes the presence at the daily rounds in the ICU, cooperation, and availability for consultations throughout the day [6].…”
Section: Introductionmentioning
confidence: 99%